2020
DOI: 10.3390/ijms21186913
|View full text |Cite
|
Sign up to set email alerts
|

3D Bone Morphology Alters Gene Expression, Motility, and Drug Responses in Bone Metastatic Tumor Cells

Abstract: Patients with advanced skeletal metastases arising from primary cancers including breast, lung, and prostate suffer from extreme pain, bone loss, and frequent fractures. While the importance of interactions between bone and tumors is well-established, our understanding of complex cell–cell and cell–microenvironment interactions remains limited in part due to a lack of appropriate 3D bone models. To improve our understanding of the influence of bone morphometric properties on the regulation of tumor-induced bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Recently, Waning et al [108] demonstrated that TGFβ released from bone also contribute to muscle weakness in an in vivo model of bone metastases. In line with this, inhibition of TGFβ and its signaling pathway leads to increased bone mass [109] , thus paving the way for possible therapeutic applications [110,111] .…”
Section: Taking Advantage Of the Pre-metastatic Niche: How Cancer Cells Home To Bonementioning
confidence: 83%
“…Recently, Waning et al [108] demonstrated that TGFβ released from bone also contribute to muscle weakness in an in vivo model of bone metastases. In line with this, inhibition of TGFβ and its signaling pathway leads to increased bone mass [109] , thus paving the way for possible therapeutic applications [110,111] .…”
Section: Taking Advantage Of the Pre-metastatic Niche: How Cancer Cells Home To Bonementioning
confidence: 83%
“…Genetics and gene expression are one of the main factors used to investigate changes in diseases. Studies investigating prostate cancer bone metastases and tumour-induced bone diseases (TIBD) have reported variations in the expression of genes when compared in 2D than in 3D [96,97], further outlining the need for 3D in vitro models.…”
Section: Scaffolds For Bone Regenerationmentioning
confidence: 99%
“…The decellularized matrices can also be used to coat scaffold biomimics, allowing for a more accessible comparison of ECM effects in different disease states [81]. Scaffolds were also used to study bone metastasis in vitro and in vivo to determine how changes in pore size and rigidity affect myeloid cell infiltration, gene expression, and drug response [82]. These advancements in analysis approaches have inspired new uses for oncomaterials in monitoring disease progression and treating patients [83].…”
Section: Trends In Cell Biologymentioning
confidence: 99%